Exploring Prospective Mathematics Teachers' Skills in Designing Innovative Technology-Based Mathematics Teaching - Tatag Yuli Eko Siswono; Agung Lukito; Hutkemri Zulnaidi; Dayat Hidayat; Sugi Hartono; Namirah Fatmanissa (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
The growing availability of technology offers opportunities to enhance mathematics teaching and learning. For mathematics educators, technology can serve as a form of instructional innovation alongside other indicators of innovative practice, such as student-centered learning, the use of real-world contexts, active concept construction, problem-solving, interaction, and the promotion of students’ motivation and attitudes. This study aims to describe mathematics teachers’ skills in designing innovative technology-based mathematics learning. A descriptive–exploratory mixed-methods approach was employed involving 20 mathematics teachers enrolled in a Mathematics Education graduate program. Quantitative data were collected through questionnaires examining perceptions of the importance and use of technology in mathematics learning. Qualitative data were obtained from lesson plan design tasks and semi-structured interviews and analyzed using indicators of innovative mathematics learning. The results show that 93.8% of participants perceived technology as necessary in mathematics learning; however, 68.8% primarily used it to verify solutions after manual completion, and 25% believed that direct technology use might hinder conceptual understanding. Analysis of lesson plans revealed the use of GeoGebra, Scratch, YouTube, and online applications. Overall, participants demonstrated varying levels of skill, with strengths in basic technology use and student-centered approaches but limited evidence of transformative pedagogical integration.